Atmosphere and Religion: The Phenomenology of Hermann Schmitz and the Possibility for a Comparative Study of Religion - Kajitani, Shinji (Religija ir kultūra, 2016)
[full article, abstract in English; abstract in Lithuanian] On the basis of his phenomenological theory of body and emotion, and especially his concept of emotion as atmosphere, Hermann Schmitz (1928–) defines religion as “behavior derived from affectedness by the divine,” i.e., communication with a powerful atmosphere overwhelming human beings. This definition enables us to explore religion in a broader context, such as dwelling, daily practice, rituals, architecture, art, etc. From this perspective, religion cannot be confined to the fields of theory, practice, institution, or convention but covers a much richer field in life. On the other hand, this view means that our daily existence is more profoundly related to the religious. This makes it understandable why new religious movements appear repeatedly, and why social phenomena appear that are not called religions but have some religious aspects even in a modern, secularized society. In this way, the theory of atmosphere can give us insight into the general necessity of the religious for human existence in each culture. Schmitz’s phenomenology of religion has, therefore, its advantage in the analysis of folk religion, which is rooted more deeply in folk culture and such of its aspects as customs, festivals, and folklore. This article will address some characteristics of Japanese folk religion and then compare monotheism with polytheism.